Corporate Governance Country Assessment : Republic of the Philippines - World Bank (Washington, DC, 2013)
Corporate governance in the Philippines is characterized by concentrated ownership by a limited number of family shareholders, within a bank-dominated financial market. A comprehensive set of corporate law and capital market regulations are enforced by relatively weak institutions that are undergoing restructuring reforms. As in many East Asian countries, the need to strengthen corporate governance was highlighted during the financial crisis in the region, and recent securities market scandals. This report benchmarks Philippine corporate governance against the OECD Principles of Corporate Governance, which have been recognized as one of the core standards underpinning the international financial architecture. As such, the report focuses primarily on corporate governance issues affecting listed companies and equity providers. Recommendations on related corporate governance issues such as banking and the governance of group structures, though relevant to the reform dialogue, are beyond the scope of this report. (Two parallel ROSCs are being prepared to assess the Philippines on accounting and auditing, and insolvency and creditor rights, which will provide greater detail on these issues.) The policy recommendations in this ROSC are intended to highlight areas in which the Philippine corporate governance system could be strengthened. They are grouped under four main headings: improving the disclosure of non-financial information, strengthening the rights of (minority) shareholders, enhancing the role of the board of directors, and ensuring the independence of the audit.